Optimum Cooling of Data Centers Application of Risk Assessment and Mitigation Techniques - Dai, Jun (Springer New York : Imprint: Springer, 2014)
This book provides data center designers and operators with methods by which to assess and mitigate the risks associated with utilization of optimum cooling solutions. The goal is to provide readers with sufficient knowledge to implement measures such as free air cooling or direct liquid immersion cooling properly, or combination of existing and emerging cooling technologies in data centers, base stations, and server farms. This book also: Discusses various telecommunication infrastructures, with an emphasis on data centers and base stations Covers the most commonly known energy and power management techniques, as well as emerging cooling solutions for data centers Describes the risks to the electronic equipment fitted in these installations and the methods of risk mitigation Devotes  a particular focus to an up-to-date review of the emerging cooling methods (such as free air cooling and direct liquid immersion cooling) and tools and best practices for designers, technology developers, installation operators, and owners Informs installation designers and manufacturers of the benefits and limitations of the most common existing and emerging cooling methods Optimum Cooling of Data Centers: Application of Risk  Assessment and Mitigation Techniques is an ideal book for researchers and engineers interested in design,  manufacturing, and optimum operation  of cooling solutions for telecom and other mission-critical infrastructures.